Life cycle assessment of auto-tropically cultivated economic microalgae for final products such as food, total fatty acids, and bio-oil - Zhang, Dan; An, Siyuan; Yao, Rao; Fu, Wen; Han, Yujie; Du, Ming; Chen, Zixi; Lei, Anping; Wang, Jiangxin (Frontiers in Marine Science, 2022)
Life cycle assessment (LCA) is one of the most attractive tools to ensure environmentally sustainable production/consumption of various goods/services. Microalgae are tiny factories and renewable, sustainable, and economical sources of biofuels, bioactive medicinal products, and food ingredients. Nowadays, microalgae are also valuable for the mitigation of elevated CO2 levels and treatment of wastewater. LCA evaluation was limited and separated, majorly in microalgal biofuels and heterotrophic cultivation. Comparative LCA for different final algal products such as algal powder, bio-oil, total fatty acid, and residue recycling is still limited, especially autotrophic microalgal cultivation for products other than bio-oils and biofuels. Thus, we chose several autotrophic cultivated microalgae, such as Haematococcus pluvialis, Desmodesmus subspicatus, and Nannochloropsis oceanica. We made a comparative LCA analysis among these selected species and a detailed step-by-step production in Chlorella sp. Our results indicated that we could significantly reduce the production cost and lower environmental impacts by selecting algal species, optimum microalgae cultivation, biomass separation, and drying process using mainly wastewater for microalgae cultivation, carefully final products selection, and land selection plus electricity renewable energy, together thermal power plants nearby for CO2 or flu gas. It shed light on the insight of microalgae consumption selection under current international requirements and challenges for carbon sequestration.